The diagnosis conundrum: Comparison of crowdsourced and expert assessments of toddlers with high and low risk of autism spectrum disorder. Issue 12 (26th November 2018) - Myers, Emily; Stone, Wendy L.; Bernier, Raphael; Lendvay, Thomas; Comstock, Bryan; Cowan, Charles
Abstract : As the diagnosis and treatment of Autism Spectrum Disorder (ASD) becomes a greater public health concern, access to professionals and expert assessment becomes increasingly more challenging. Novel techniques to improve efficiency of assessment of young children with social communication concerns are desperately needed to address significant barriers to accessing diagnostic evaluations. Utilizing crowdsourcing technology, we compared ratings by experts and crowdworkers of social communication behaviors in videos of 18‐month‐old children. Of note, 563 crowdworkers and 24 expert responses were collected in approximately 7 hr and 57 days, respectively. Summed scores of social communication behaviors observed by crowdworkers showed high correlation to those of experts. These data introduce a novel and perhaps efficient way in which to examine of social communication impairments in toddlers. Autism Research 2018, 11: 1629–1634 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This research compared crowdsourced assessments of social communication behaviors to assessments by experts, for toddlers whose behaviors ranged in severity from typical to atypical. Results showed that crowdsourced rankings of social communication behavior significantly correlate with those of experts.